ANALISIS FAKTOR PENURUNAN PENYALURAN PEMBIAYAAN FINTECH SYARIAH DI INDONESIA TAHUN 2025 - Muhammad Fauzan; Surya Tegar Widjiantoro (STAI Sulthan Syarif Hasyim, 2025)
This study focuses on the notable decline in Islamic fintech financing in 2025, a development that becomes more striking when viewed alongside the simultaneous increase in the industry’s total assets. Official data from OJK indicate a sharp contraction, with financing dropping from Rp 1.58 trillion in 2024 to Rp 800 billion in 2025, suggesting deeper structural issues within the Islamic fintech ecosystem. Using a qualitative approach through a literature review, this research explores how rising credit risk—as reflected in the increase of TWP90—diminishing digital trust due to information uncertainty, weakening purchasing power, and stricter regulatory requirements collectively shaped lenders’ decisions to reduce funding supply. The synthesis of findings reveals that credit risk and digital trust play the most decisive roles in constraining financing flows, particularly in sharia-based platforms that rely heavily on transparency and contractual clarity. These results reinforce the relevance of the Crisis–Trust Model of Islamic Fintech in explaining shifts in funding behavior and highlight the need for stronger governance, improved digital transparency, and more adaptive regulatory policies to restore stability and resilience in the Islamic fintech industry.